Immunoexpression of pRb and EGFR using tissue microarray (TMA) technique - a preliminary study - Kipli, N.P.; Cheong, C.S.; Zain, R.B.; Hamid, S.; Lim, K.P.; Abraham, T.; Ismail, M.S.; Hussaini, H.M. (Wiley, 2006)
Purpose: To assess the expression of pRb and EGFR in oral epithelial lesions using TMA technique. Methods: Paraffin embedded specimens were selected from the archives of the Diagnostic Laboratories at the Faculty of Dentistry, University of Malaya and Universiti Kebangsaan Malaysia. Selected epithelial areas were cored and developed into tissue microarray blocks. A total of 32 samples for pRb and 50 samples for EGFR were analysed using immunohistochemical techniques. Results: Abnormal pRb staining (1? or less) was seen in 80% (8/10) OSCC, 38.5% (5/13) dysplastic and 22.2% (2/9) normal/hyperplastic epithelium. Positive EGFR staining was observed in 25/35 (71.4%) OSCC cases with 11 cases (31.4%) showing staining of 2? or more. Out of 5 epithelial dysplasia and 10 normal/hyperplastic epithelium, positive EGFR staining was noted in 3 (60%) and 8 (80%) cases respectively. Interestingly, only 1(20%) epithelial dysplasia and 1(10%) normal/hyperplastic epithelium showed staining of 2? or more. Conclusion: High frequency of abnormal expression of pRb is observed in OSCC cases as compared to dysplastic and normal/hyperplastic epithelium. EGFR is expressed in OSCC as well as epithelial dysplasia and normal/hyperplastic epithelium. However, higher EGFR positivity is more common in OSCC cases. This study supports the feasibility and ease of using TMA technique for immunohistochemical studies.